Capital rules The construction of global finance - Neha Arora (New Delhi Random Publications, 2021)
Role of capital market; manage evolving mix of global and European banking system; capital structure and film value; european monetary system; global markets and economy; global financial system; financial institutions in 21st century.
Keywords: Financial economics